Optimal Ratio of DHA to EPA Enriched in Rotifer Brachionus rotundiformis and Brine Shrimp Artemia spp. for Feeding Blue Swimming Crab Portunus pelagicus Larvae - ภัทรธำรง , ปริยภัทร; ปิยะธีรธิติวรกุล, สมเกียรติ; ธนาสมหวัง, วารินทร์; อุนะกุล , พนิดา (KKU Science Journal, 2012)
An optimal ratio of high polyunsaturated fatty acids, DHA to EPA enriched in rotifer Brachionus rotundiformis and brine shrimp Artemia spp. for feeding blue swimming crab Portunus pelagicus larvae was carried out. Nine different ratios of DHA:EPA; 1:1, 1:2, 1:3, 2:1, 2:2, 2:3, 3:1, 3:2, and 3:3 were enriched to rotifer and brine shrimp for 12 hours and then harvested to feed different larval stages of P. pelagicus; from hatched eggs, zoea 1-2 and zoea 3- first crab. The results showed that DHA:EPA 2:2 and DHA:EPA 3:2 gave the best survival rate for zoea 1 to first crab 24.44 .5.56% and 24.44 .8.89% respectively. DHA:EPA 3:3 gave the shortest intermolt period in stages of zoea 2, 3, and 4.